2019
DOI: 10.1158/0008-5472.can-18-2693
|View full text |Cite
|
Sign up to set email alerts
|

ROCK Inhibition Induces Terminal Adipocyte Differentiation and Suppresses Tumorigenesis in Chemoresistant Osteosarcoma Cells

Abstract: Tumors comprise heterogeneous cell types including cancer stem cells (CSC), progenitor cells, and differentiated cells. Chemoresistance is a potential cause of relapse and a key characteristic of CSC, but the development of novel therapeutic approaches for targeting these cells has been limited. We previously established osteosarcoma-initiating (OSi) cells by introducing the gene for c-Myc into bone marrow stromal cells of Ink4a/Arf knockout mice. These OSi cells are composed of two distinct clones: highly tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…The present study indicated that KD025 treatment may be an effective inhibitor for reversing MDR in leukemia cell lines. These results were consistent with other previous studies on the ROCK signaling pathway in leukemia (41,45). However, the reversal efficiency and mechanism of KD025 treatment in ABCG2-mediated MDR remains unclear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study indicated that KD025 treatment may be an effective inhibitor for reversing MDR in leukemia cell lines. These results were consistent with other previous studies on the ROCK signaling pathway in leukemia (41,45). However, the reversal efficiency and mechanism of KD025 treatment in ABCG2-mediated MDR remains unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the ROCK pathway was also discovered to serve an important role in physiological conditions and the abnormal activation of myeloproliferative diseases (40). A previous study demonstrated that ROCK inhibition effectively reduced leukemic cell proliferation (41). Therefore, the deregulation of ROCK signaling is emerging as a potential key target in leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Another differentiation approach has been described in osteosarcoma. Inhibition of Rho-associated coiled-coil containing protein kinase (ROCK) by fasudil caused terminal adipocyte differentiation in chemotherapy-resistant OS CSCs [120]. This approach takes advantage of the pluripotency of CSCs to induce their trans-differentiation into another lineage; however, its therapeutic value is still unknown in STS.…”
Section: Differentiation Therapymentioning
confidence: 99%
“…The inhibitory effect of NSC23766 on terminal adipogenesis might therefore have been due to the activation of RhoA. We previously showed that treatment with Y‐27632 or fasudil as specific inhibitors of the downstream RhoA effector ROCK drives adipogenesis in DFAT cells, 3T3‐L1 preadipocytes, or osteosarcoma cells through negative regulation of MKL1 associated with F‐actin depolymerization, similar to the effect of LatA (Nobusue et al, ; Takahashi et al, ). We therefore next examined the effects of both ROCK and Rac1 inhibitors on adipogenesis in DFAT cells.…”
Section: Resultsmentioning
confidence: 93%